THE APPLICATION OF CRIMINAL SANCTIONS AGAINST PERPETRATORS OF POLITICAL DOWRY PRACTICES IN REGIONAL HEAD NOMINATIONS - Iskandar, Iskandar; Hadad, Alwi Al (Jurnal Politik Pemerintahan Dharma Praja, 2024)
Political money practice in regional head nominations poses a serious threat to the integrity of democracy and political stability in Indonesia. Political money undermines the electoral process by prioritizing money over competence, resulting in leaders who are more focused on recovering their political investments rather than on public service. This research aims to analyze the impact of implementing criminal sanctions on political money practitioners in maintaining political stability and the quality of democracy at the regional level. The method used is normative juridical, with a legislative and conceptual approach. The research findings indicate that the application of criminal sanctions acts as a deterrent, enhances electoral integrity, strengthens public trust in democracy, reduces corruption, and promotes equal opportunities for competent candidates. However, challenges such as difficulties in proving violations and weak oversight remain obstacles to the effective implementation of sanctions. Therefore, strict and consistent law enforcement is necessary to create fair, clean, and transparent elections and to maintain local political stability.